Autonorama : the illusory promise of high-tech driving - Norton, Peter (Island Press, 2021)
"The foundation has been laid for fully autonomous," Elon Musk announced in 2016, when he assured the world that Tesla would have a driverless fleet on the road in 2017. "It's twice as safe as a human, maybe better." Promises of technofuturistic driving utopias have been ubiquitous wherever tech companies and carmakers meet. In Autonorama: The Illusory Promise of High-Tech Driving, technology historian Peter Norton argues that driverless cars cannot be the safe, sustainable, and inclusive "mobility solutions" that tech companies and automakers are promising us. The salesmanship behind the driverless future is distracting us from investing in better ways to get around that we can implement now. Unlike autonomous vehicles, these alternatives are inexpensive, safe, sustainable, and inclusive. Norton takes the reader on an engaging ride --from the GM Futurama exhibit to "smart" highways and vehicles--to show how we are once again being sold car dependency in the guise of mobility. He argues that we cannot see what tech companies are selling us except in the light of history. With driverless cars, we're promised that new technology will solve the problems that car dependency gave us--zero crashes! zero emissions! zero congestion! But these are the same promises that have kept us on a treadmill of car dependency for 80 years. Autonorama is hopeful, advocating for wise, proven, humane mobility that we can invest in now, without waiting for technology that is forever just out of reach. Before intelligent systems, data, and technology can serve us, Norton suggests, we need wisdom. Rachel Carson warned us that when we seek technological solutions instead of ecological balance, we can make our problems worse. With this wisdom, Norton contends, we can meet our mobility needs with what we have right now